The Funambulist Papers 2 - Lambert, Léopold (punctum books, 2015)
This book is the second volume of texts curated specifically for The Funambulist since 2011. The editorial line of this second series of twenty-six essays is dedicated to philosophical and political questions about bodies. This choice is informed by Léopold Lambert's own interest in the (often violent) relation between the designed environment and bodies. Corporeal politics do not exist in a void of objects, buildings and cities; on the contrary, they operate through the continuous material encounters between living and non-living bodies. Several texts proposed in this volume examine various forms of corporeal violence (racism, gender-based violence, etc.). This examination, however, can only exist in the integration of the designed environment's conditioning of this violence. As Mimi Thi Nguyen argues in the conclusion of this book's first chapter, "the process of attending to the body - unhooded, unveiled, unclothed - cannot be the solution to racism, because that body is always already an abstraction, an effect of law and its violence." Although the readers won't find indications about the disciplinary background of the contributors - the "witty" self-descriptions at the end of the book being preferred to academic resumés - the content of the texts will certainly attest to the broad imaginaries at work throughout this volume. Dialogues between dancers and geographers, between artists and biohackers, between architects and philosophers, and so forth, provide the richness of this volume through difference rather than similarity. The Funambulist Papers are published by the CTM Documents Initiative imprint, Center for Transformative Media, Parsons School of Design, The New School. CTM is a transdisciplinary media research initiative bridging design and the social sciences, and dedicated to the exploration of the transformative potential of emerging technologies upon the foundational practices of everyday life across a range of settings.